2005
DOI: 10.1073/pnas.0410006102
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist of growth hormone-releasing hormone induces apoptosis in LNCaP human prostate cancer cells through a Ca 2+ -dependent pathway

Abstract: growth hormone-releasing hormone antagonist ͉ growth hormone-releasing hormone receptor ͉ calcium ͉ cancer therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 57 publications
2
25
0
1
Order By: Relevance
“…This may cause some saturation in the corresponding signaling pathways and, after supplementation with exogenous GHRH, results in their down-regulation. Considering the recently reported antiapoptotic effect of GHRH on cancer cells (21), it could be argued that serum deprivation may be sufficient to trigger apoptosis in MCF-7 cells, thus complicating the interpretation of our experimental results. However, apoptosis appears unlikely because, under our experimental conditions, no evidence of cell death was noted after 4 days of culture in the absence of serum, despite the dramatic reduction in the baseline levels of cell proliferation.…”
Section: Discussionmentioning
confidence: 93%
“…This may cause some saturation in the corresponding signaling pathways and, after supplementation with exogenous GHRH, results in their down-regulation. Considering the recently reported antiapoptotic effect of GHRH on cancer cells (21), it could be argued that serum deprivation may be sufficient to trigger apoptosis in MCF-7 cells, thus complicating the interpretation of our experimental results. However, apoptosis appears unlikely because, under our experimental conditions, no evidence of cell death was noted after 4 days of culture in the absence of serum, despite the dramatic reduction in the baseline levels of cell proliferation.…”
Section: Discussionmentioning
confidence: 93%
“…The inhibitory actions of GHRH antagonists on tumor growth are thought to be mediated by the pituitary type GHRHReceptor and its splice variant-1 (SV-1), which is generated by alternative splicing from the GHRH receptor gene. 6,7 Thus, we have recently reported that human colon cancer cells, in contrast Bcl-2 was diminished after 10 min, followed by an increase in cleaved caspase-9 after 30 min, cleaved caspase-3 after 60 min and finally PARP cleavage, which started to rise 2 hr after addition of JMR-132 to the media.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that GHRH antagonists induce apoptosis in LNCap human prostate cancer cells through an elevation in intracellular free Ca 2+ levels. 7 In human endometrial HEC-1A cancer cells, apoptosis induced by GHRH antagonist was followed by an increase in protein expression of the intrinsic and extrinsic pathway of apoptosis. 8 Recent findings, that silencing of p21…”
Section: Introductionmentioning
confidence: 99%
“…Hypothalamic neurohormone GHRH and GHRH-R are not confined to the hypothalamic-pituitary axis, however, but are also produced by various extrahypothalamic sites. GHRH/GHRH-R modulates cell proliferation and apoptosis in many tissues, including prostate (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…In prostate cancer, GHRH antagonist JV-1-38 induces apoptosis in the LNCaP cell model through a calcium-dependent mechanism (11). In models of CRPC, GHRH antagonist JMR-132 suppresses AKT and ERK signaling cascades, thereby decreasing cell proliferation and survival (13).…”
mentioning
confidence: 99%